Análise ergonômica do trabalho na execução de armaduras - Carvalho, Laísa Cristina (2016)
Civil construction is one of the activities that generates most jobs in the country, owning handmade construction methods and with few technological innovations. It notes that the number of workers in that area is significant because of the diversity of existing activities in a building. In the case of the reinforcing steel service, tasks are performed manually and request different degrees of effort, which when applied recursively, with tools and equipment unsuitable and inadequate workplace, may cause damage to the health and comfort of workers. In this context, this study aims to evaluate the ergonomic working conditions of the reinforcing steel service. Therefore, we used the methodology of the Ergonomic Assessment Method for Task Analysis (AET), aided by three ergonomic tools: Ergonomic Workplace Analysis (EWA), the Metabolic Equivalent of Task (MET) and the Occupational Repetitive Actions (OCRA). Considering these factors analyzed, with photographic records, interviews and site visiting to watch the worker during his tasks, the actual conditions of the job were studied, trying to analyze everyday work situations, health and safety of workers and featuring, thus, the workplace conditions during reinforcing steel service. The results corroborate the existence of working inadequate postures while performing the task. According to ergonomic tool EWA the most critical ergonomic factor detected was related to Working Postures and Movement, followed by Load Lifting factor. Among the activities analyzed using this ergonomic analysis instrument, the one which presented more critic was related to the assembly of reinforcement for beams. According to the ergonomic analysis instrument MET, tasks with higher energy expenditure and metabolic expenditure were related to Receiving and Storage of steel bars. Among the operation inherent to each task of reinforcement service, there is the tie bars with annealed wire. Finally, it is concluded that the index of exposure OCRA for the activity of tie bars with annealed wire presents imminent risk to all analyzed situations.